Tyrian purple in archaeological textiles: DMF extraction and recrystallization for the Raman identification of precursors and derivatives. (13th January 2017) - Doherty, Brenda; Nowik, Witold; Miliani, Costanza; Clementi, Catia
Abstract : The prized ancient dyestuff, Tyrian purple, has been extensively and widely studied by multiple spectroscopic and chromatographic methods alike. In this paper, an extraction method adopted by liquid chromatography by using N, N ‐dimethylformamide is proposed as a sample pre‐treatment for the characterization of minor reference brominated and unsubstituted isatin and indirubin components by micro‐Raman spectroscopy. The method has been validated for the identification of these constituents in accordance with HPLC PDA measurements on a series of Tyrian purple‐dyed wool, silk and cotton textiles and in archaeological samples from the Roman period. It results specifically effective in cases when high‐scattering dibromoindigoids are not revealed and when main indigoid spectral features, seemingly of plant origin, can only be reasonably hypothesized by conventional Raman. This method also innovatively highlights the possible presence of carotenoids and porphyrin‐type copper and iron complexes, noted in marine molluscs, and potentially opening a new perspective to the current diagnostics of Tyrian purple through its biomarkers in the cultural heritage domain. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : In this work, a micro‐Raman sample pre‐treatment is proposed for the characterization brominated and unsubstituted isatins and indirubins, the minor components of Tyrian purple. Highlights include the hypothesized presence of carotenoids, porphyrin‐type copper and iron complex biomarkers. The method has been validated for a series of reference textiles and archaeological samples in accordance with HPLC photodiode array.